17-2(1-3x)4=5

Simple and best practice solution for 17-2(1-3x)4=5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 17-2(1-3x)4=5 equation:


Simplifying
17 + -2(1 + -3x) * 4 = 5

Reorder the terms for easier multiplication:
17 + -2 * 4(1 + -3x) = 5

Multiply -2 * 4
17 + -8(1 + -3x) = 5
17 + (1 * -8 + -3x * -8) = 5
17 + (-8 + 24x) = 5

Combine like terms: 17 + -8 = 9
9 + 24x = 5

Solving
9 + 24x = 5

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + 24x = 5 + -9

Combine like terms: 9 + -9 = 0
0 + 24x = 5 + -9
24x = 5 + -9

Combine like terms: 5 + -9 = -4
24x = -4

Divide each side by '24'.
x = -0.1666666667

Simplifying
x = -0.1666666667

See similar equations:

| h(-3)=-3 | | 8(-3n-7)+6(6+4n)=-24 | | -9h+32=-67 | | 5-m=131 | | 11x^2=5x-3 | | 16+3x=7x-3 | | 4x^3+5x^2+2x+16=X+2 | | 10x+15+6x-11=180 | | 3x^2+5x=16 | | 4x^3+5x^2+2x+16= | | 3x*2+5x=16 | | 36=-3(k-6) | | y=-0.05x^2+1.25x | | 3(2x+9)=-15 | | 3(w-11)=15 | | 18z-17z+3=17 | | 10-2r=6 | | -6.8(2p+5)-1.6(4p+6)= | | T=24m-4m^2 | | 16=4(n+1) | | h(-4)=-5 | | ix^2-8x+30=0 | | (7x^4+xy^2)dx+(x^2y+6y^5)dy=0 | | x=172+-3x | | 8(x+6)-24=4(2x+5) | | x=172+3x | | x=172 | | -6t^2+24t+14=t | | 2x-5y=36 | | 2x-17=-17+x+2 | | -(6-(a+1))=9-(5-(2a-3)) | | 10=2(h+2) |

Equations solver categories